Vascular fibrinoid necrosis in the urinary bladder of ketamine abusers: A new finding that may provide a clue to the pathogenesis of ketamine‐induced vesicopathy. Issue 2 (11th March 2018) - Chen, Yen‐Chang; Jhang, Jia‐Fong; Hsu, Yung‐Hsiang; Kuo, Hann‐Chorng
Abstract : Two 31‐year‐old women who had abused ketamine, 1 for 8 years and 1 for 5 years, presented with ketamine‐induced vesicopathy with urinary frequency, decreased bladder capacity, and detrusor overactivity. An enterocystoplasty was performed in both cases. The pathology of the urinary bladders in both women showed ulcerative cystitis and fibrinoid necrosis of vessels; the latter was confirmed by Masson trichrome staining. Fibrinoid necrosis of vessels is a kind of immune complex‐mediated vasculitis that induces the release of inflammatory mediators, with subsequent thrombosis, ischemic injury, and eventual tissue necrosis in localized areas, the so‐called Arthus reaction. The new finding of fibrinoid necrosis in the urinary bladders of ketamine abusers may provide a new clue to the pathogenesis of ketamine‐induced vesicopathy.